Cash by any other name? Evidence on labelling from the UK Winter Fuel Payment - Timothy K. M. Beatty; Laura Blow; Thomas F. Crossley; Cormac O'Dea (Institute for Fiscal Studies (IFS), 2011)
Standard economic theory implies that the labelling of cash transfers or cash-equivalents (e.g. child benefits, food stamps) should have no effect on spending patterns. The empirical literature to date does not contradict this proposition. We study the UK Winter Fuel Payment (WFP), a cash transfer to older households. Exploiting sharp eligibility criteria in a regression discontinuity design, we find robust evidence of a behavioural effect of the labelling. On average households spend 41% of the WFP on fuel. If the payment was treated as cash, we would expect households to spend approximately 3% of the payment on fuel.
Keywords: D12; H24; 330; labelling; benefits; expenditure; Sozialpolitik; Öffentliche Sozialleistungen; Privater Haushalt; Alte Menschen; Konsumentenverhalten; Großbritannien